Формування практичної підготовленості майбутніх офіцерів до організації форм фізичної підготовки із військовослужбовцями різних вікових груп - Пришва, О. Б.; Pryshva, O. B.; Бутенко, А. Є.; Butenko, A. Ye.; Нестеров, О. С.; Nesterov, O. S.; Гром, Т. В.; Hrom, T. V.; Грицай, В. В.; Hrytsai, V. V.; Павлов, Р. В.; Pavlov, R. V. (Науковий часопис НПУ імені М. П. Драгоманова. Серія 15: Науково-педагогічні проблеми фізичної культури (фізична культура і спорт). - 2024. - Вип. 2(174). - С. 156-163, 2024)
Наголошено, що головною метою дослідження є розроблення організаційно-педагогічних умов формування практичної підготовленості майбутніх офіцерів у напрямі організації ними форм фізичної підготовки (на прикладі курсантів вищих військових навчальних закладів Національної гвардії України). В результаті теоретичного дослідження розроблені організаційно-педагогічні умови формування практичної підготовленості майбутніх офіцерів у напрямі організації ними форм фізичної підготовки із акцентованим використанням сучасних технічних засобів навчання та фітнес-технологій із майбутнім підлеглим особовим складом. Перспективи подальших досліджень передбачають проведення апробації запропонованих нами організаційно-педагогічних умов.

According to the results of the analysis of the scientific and methodical literature, it was established that an insufficient number of scientific and methodical works are devoted to the actual issue of the formation of theoretical knowledge and practical skills of the organization of the physical training system with the future subordinate staff by those obtaining higher education of higher military educational institutions. The main goal of the study is to develop organizational and pedagogical conditions for the formation of practical training of future officers in the direction of their organization of forms of physical training with an emphasis on the use of modern technical means of training and fitness technologies. As a result of theoretical research, we have developed organizational and pedagogical formations of practical training of future officers in the direction of their organization of forms of physical training (with an emphasis on the use of modern technical means of training and fitness technologies) with future subordinate personnel. We expect that the introduction of the proposed organizational and pedagogical conditions into the system of physical and special physical training of the representatives of the studied category will contribute to the formation of theoretical knowledge and practical skills of organizing forms of physical training with servicemen of different age groups (categories). In addition, in the future it is possible for future officers to organize occupational therapy activities with military personnel of various categories after treatment of injuries, illnesses, and wounds.

Отмечено, что главная цель исследования - разработка организационно-педагогических условий формирования практической подготовленности будущих офицеров в направлении организации ими форм физической подготовки (на примере курсантов высших военных учебных заведений Национальной гвардии Украины). В результате теоретического исследования разработаны организационно педагогические условия формирования практической подготовленности будущих офицеров в направлении организации ими форм физической подготовки с акцентированным использованием современных технических средств обучения и фитнес-технологий с будущим подчиненным личным составом.
Formation of Practical Readiness of Future Officers to organize Forms of Physical Training with Servicemen of different age groups
Keywords: військово-прикладні навички; компетентності; майбутні офіцери; фізична підготовка; фізичні якості; applied military skills; competences; future officers; physical training; physical qualities; военно-прикладные навыки; компетентности; будущие офицеры; физическая подготовка; физические качества